Phylogenetic relationships between Arabidopsis and sugarcane bZIP transcriptional regulatory factors - Michel Vincentz; Paulo S. Schlögl; Luis Gustavo G. Corrêa; Fabiana Kühne; Adilson Leite (Genetics and Molecular Biology, 2001)
We built a complete and non-redundant database of bZIP transcriptional regulatory factors from the Arabidopsis reference genome. These Arabidopsis bZIP factors were ordered into thirteen families of evolutionary related proteins and this classification was used to identify and organize sugarcane cDNAs encoding bZIP proteins. We also show how this classification should help in defining putative clusters of orthologous groups of higher plant bZIP regulators and briefly discuss the expected benefits of this procedure to efficiently characterize sugarcane bZIP transcriptional regulators. Construímos um banco de referência não redundante de fatores de regulação da transcrição do tipo bZIP a partir de dados do genôma de Arabidopsis thaliana. Os fatores bZIP de Arabidopsis foram ordenados em treze famílias de proteínas evolutivamente relacionadas e essa classificação foi usada para organizar os cDNAs de cana de açúcar que codificam proteínas bZIP. Além disso, mostramos que essa classificação poderá ser útil para definir "Putative Clusters of Orthologous Groups" de reguladores bZIP de plantas superiores.